P‐52: High‐Gain Source Followers Driven by Corbino Oxide TFTs for Integrated Display Data Drivers. Issue 1 (June 2015) - Um, Jae Gwang; Geng, Di; Mativenga, Mallory; Mruthyunjaya, Ravi K.; Heiler, Gregory N.; Tredwell, Timothy J.; Jang, Jin
Abstract : A high‐gain source follower, utilizing oxide TFTs with a Corbino (circular) structure, is reported. Given the infinite output resistance exhibited by Corbino TFTs in the outer‐drain condition (i.e., when the outer electrode is biased as the drain), the Corbino TFT‐based source follower provides higher gain in operation than its rectangular TFT‐based counterparts.